DASAR IDEOLOGIS KOMUNIKASI GLOBAL DALAM PERSPEKTIF ISLAM: [Telaah atas Peran dan Posisi Islam Dalam Komunikasi Global] - Zulkarnain Zulkarnain (TASÂMUH, 2014)
Global communication is one of the emerging forces today. Its presence has in?uenced various aspects of life such as politics, economics, culture, military and so on. Policies and regulations that run in the international course is inseparable from the role of communication globally. An interesting issue to be discussed is how the position of the Islamic world to confront the issue of global communication, what is the role played by Islam in the global communications arena, as well as what to do in an effort to make Islam can play a signifcant role in the global communication?This research reveal that Islam does not have a signifcant position. Similar to the third world countries in general. They are just as many countries that rely on information provided by the West, especially the United States. In terms of the communication media, usually third world countries, including Islam, just as consumers felt that their utilization is not maximized by all citizens. Moreover, a producer in creating the communications media, it’s too much to hope for. The Implications arising from the position of Islam as it is, in the global communication course, does not have the power to play a signifcant role. The presence of Islam in the new global communications limited discourse that has great potential to rise. Media are widely used by Iran in building its revolution as expressed by Majid Tehranian in his book Global Communication and World Politics has not given a role in the global arena. Likewise, news agencies that exist in the Arab countries have not been able to become a major supplier of news among the Muslim community and the world community